Adjuvant Chemotherapy for Early Stage Non-Small Cell Lung Cancer - Patel, Manali; Wakelee, Heather A. (Frontiers in Oncology, 2011)
For many years adjuvant chemotherapy has been a standard treatment after complete resection in malignancies such as breast and colon but only recently has its use become standard in early stage non-small cell lung cancer (NSCLC). Although surgery is regarded as the best possible treatment for early stage NSCLC, only 20-25% of patients have resectable disease at presentation. Despite optimal surgical treatment, five-year survival rates for NSCLC remain 50-60% for stage IB, 40%-50% for stage II, and 20-30% for stage III (Kohler 2011; Siegel 2011). Adjuvant chemotherapy provides additional survival benefit in resected NSCLC but questions remain as to how to select patients for therapy and which regimen is best. Other than work with tegafur/uracil in Japan, the positive adjuvant trials have all utilized a cisplatin backbone, but the drug(s) to pair with cisplatin are a matter of debate and will be discussed further in this manuscript.